Comparative Analysis of Clinical and Functional Results of Standard and Modified Endothelial and Descemet Membrane Transplantation Techniques - B. E. Malyugin; A. M. Gelyastanov; O. P. Antonova; A. V. Belodedova; A. A. Khaletskaya (Oftalʹmologiâ, 2023)
Purpose: to evaluate the clinical and functional results of two methods of Descemet’s membrane endothelial keratoplasty using a full and half graft.Patients and methods. This study is based on surgical treatment of 54 patients (54 eyes) with cataracts and Fuchs endothelial corneal dystrophy were divided into two groups. In the first one, phacoemulsification of cataract with implantation of a hydrophobic IOL and standard «classical» technique of Descemet’s membrane endothelial keratoplasty were performed, it included 30 patients (30 eyes). The second group underwent cataract phacoemulsification with implantation of a hydrophobic IOL and modified transplantation of a fragment (1/2) of Descemet’s membrane, it included 24 patients (24 eyes).Results. Transparent engraftment in the first group was achieved in 100 % of cases (30 out of 30 patients), in the second group in 95.8 % of cases (23 out of 24 patients). It should be noted that in the second group, one patient had fibrosis of the posterior layers of the corneal stroma (due to incomplete adherence of the DM to the posterior surface of the recipient’s cornea), this complication required endothelial re-keratoplasty. After 12 months, the BCVA improved from 0.2 ± 0.1 to 0.8 ± 0.2 in the first group, from 0.1 ± 0.1 to 0.7 ± 0.2 in the second group (p < 0 ,0001). The central corneal thickness (CCT) according to keratopachymetry in the first group decreased from 648.7 ± 60 to 512.4 ± 27.4 μm, in the second group — from 650.9 ± 44.5 to 519.6 ± 43.9 μm respectively. The endothelial cell loss (ECL) was 52.3 % and 54.9 % in the first and second groups respectively.Conclusion. The modified technique of Descemet’s membrane endothelial keratoplasty is effective for the treatment of Fuchs’ endothelial corneal dystrophy providing high clinical and functional results. A comparative analysis of the results obtained showed that at all results of BCVA, ECC and CCT by 12 months after surgery were comparable between two groups. Thus, the use of the new technique made it possible to double the availability of donor material and provide patients good clinical outcomes comparable to those of «classical» DMEK.